Autotransplantatıon Of An Impacted Maxıllary Canıne (A Case Report) - Aslıhan M. Ertan Erdinç; Hakan Bulut (Galenos Yayinevi, 2000)
It's possible to gain impacted teeth to the dental arch by orthodontic treatment. But, deviations from normal positions of those teeth, makes orthodontic repositioning impossible. In cases where orthodontic repositioning is impossible, allotransplantation is used as an alternative method. Crown of an impacted left maxillary canine of a 20 year old male patient is exposed by surgery and the tooth is tried to be positioned properly to the maxillary arch. At the end of the 1st year, the expected movement was not achieved and the tooth was brought to alignment by means of autotransplantation.